The Effect of a Problem-Based Learning Model Supported by the Wordwall Media on The Science Learning Outcomes of Fifth-Grade Students at Santo Ignatius Private Elementary School in Medan Academic Year 2025/2026 - Mardiana Mardiana; Jhonas Dongoran; Yanti Vidarosa Naibaho; Rumiris Lumban Gaol; Irmina Pinem (International Journal Labs, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall media on the learning outcomes of fifth-grade students of Santo Ignatius Private Elementary School, Medan, in the 2025/2026 academic year. This study was motivated by the low student learning outcomes caused by the use of learning models that do not involve students' activeness and critical thinking skills in the learning process. This study used a pre-experimental method with a One Group Pretest-Posttest Design. The sample in this study amounted to 28 students. Data collection techniques used observation, learning outcome tests, questionnaires and documentation. Data analysis was carried out through normality tests and hypothesis tests using the Wilcoxon Signed-Rank Test. The results showed that the average pretest score was 72.5 and the average posttest score was 89.1, resulting in an increase of 16.6. The results of the normality test showed that the data were normally distributed. Furthermore, the results of the hypothesis test used the Wilcoxon Signed-Rank Test. The test results showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. Thus, Ho is rejected and Ha is accepted, indicating that the Problem-Based Learning model assisted by Wordwall media has an effect on the science learning outcomes of fifth-grade students at Santo Ignatius Private Elementary School, Medan, in the 2025/2026 academic year.